Are head-down tilt bedrest studies capturing the true nature of spaceflight-induced cognitive changes? A review - Barkaszi, Irén; Ehmann, Bea; Tölgyesi, Borbála; Balázs, László; Altbäcker, Anna (Frontiers in Physiology, 2022)
Although a number of studies have examined cognitive functions in space, the reasons behind the observed changes described by space research and anecdotal reports have not yet been elucidated. A potential source of cognitive changes is the cephalad fluid shift in the body caused by the lack of hydrostatic pressure under microgravity. These alterations can be modeled under terrestrial conditions using ground-based studies, such as head-down tilt bedrest (HDBR). In this review, we compare the results of the space and HDBR cognitive research. Results for baseline and in-flight/in-HDBR comparisons, and for baseline and post-flight/post-HDBR comparisons are detailed regarding sensorimotor skills, time estimation, attention, psychomotor speed, memory, executive functions, reasoning, mathematical processing, and cognitive processing of emotional stimuli. Beyond behavioral performance, results regarding brain electrical activity during simulated and real microgravity environments are also discussed. Finally, we highlight the research gaps and suggest future directions.